Electromagnetic form factor of the pion in the space- and time-like regions within the front-form dynamics - De Melo, J. P B C [UNESP]; Frederico, T.; Pace, E.; Salmè, G. (Elsevier, 2004)
The pion electromagnetic form factor is calculated in the space- and time-like regions from -10 (GeV/c)2 up to 10 (GeV/c)2, within a front-form model. The dressed photon vertex where a photon decays in a quark-antiquark pair is depicted generalizing the vector meson dominance ansatz, by means of the vector meson vertex functions. An important feature of our model is the description of the on-mass-shell vertex functions in the valence sector, for the pion and the vector mesons, through the front-form wave functions obtained within a realistic quark model. The theoretical results show an excellent agreement with the data in the space-like region, while in the time-like region the description is quite encouraging. © 2003 Elsevier B.V. All rights reserved.
Keywords: Electromagnetic form factors; Pion; Relativistic quark model; Vector-meson dominance; calculation; electromagnetic field; molecular dynamics; molecular model; photon; pion; space; time; waveform